The Impact of Organizational Justice on the Workplace Quality in the Ministry of Foreign Affairs in Riyadh - Filemban, Nahed Nasser; Al-Qurashi, Suzan Mohammad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the level of organizational justice and its dimensions (distributional, procedural, and transactions) from the perspective of the employees at the Ministry of Foreign Affairs in Riyadh and to identify the level of dimensions of the workplace quality (conditions of the work environment moral, job characteristics, salaries and rewards, workgroups, supervision and participation method, and decision making process) In the Ministry of Foreign Affairs from the employees’ point of view. Also, it aimed to clarify the relationship between organizational justice within its dimensions (distributional, procedural, and transactions) and workplace quality within its dimensions (moral work conditions, job characteristics, salaries and rewards, the manager’s supervision’s method, and participation in decision-making). The researcher used the descriptive-analytical method; with a population consisted of (1733) employees of the Ministry of Foreign Affairs Office in Riyadh. The study used a questionnaire that was distributed to the sample of the study which consisted of (292) employees who were randomly selected. The study has showed some results, most important of: The level of employees’ perception of organizational justice in the Ministry of Foreign Affairs in Riyadh is high, as the organizational justice is applied by (77.25%); the realization perception of procedural justice was at its highest (81%); however, the distributive justice was the least applied by (73.75%). The Ministry of Foreign Affairs in Riyadh has a high workplace quality by a quality level of (79.50%); where the work environment conditions were the highest at (82%) and the salaries and rewards were the lowest at (78.25%). The study also concluded that there was a statistically significant positive impact of the organizational justice dimensions (organizational justice, procedural justice, distributive justice) on the career’s quality (after the morale conditions of the work environment, after the characteristics of the job, after salaries and remunerations, after working groups, after the supervision method, after participating in making decisions). In addition, there was a strong positive relationship between the dimensions of organizational justice and career quality and that the three dimensions of organizational justice explain (76.8%) of the changes and positive effects that occur in the career quality. We find that distributive justice is the most important and influential on the career quality, followed by the fairness of transactions and procedural justice. In light of the results, the researcher recommended that the administration has to ensure that all employees have the same rights and privileges through employing transparency in the rewards’ provision basing on legal and fair basis for all.